Penyusunan Teks Biografi dengan Model Project-Based Learning di SMA Negeri 1 Majene - Honjong, Gusnawati (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This type of research is Classroom Action Research which aims to determine the increase in the ability to compose biographical texts using the Project Based Learning Model. The population in this study were all students in class X of State High School 1 Majene, Regency and the sample was class which is conducted. Test data on student learning outcomes were analyzed evenly, while data on student learning activities were analyzed using descriptive analysis. The results of the research show that students' composing abilities have increased. Based on data in cycle I, there were 5 students in the poor category with a score of 45 with a percentage of 13.1%, in cycle II there were 7 students in the complete category with a percentage of 18.42% and in cycle III there were 25 students in the complete category. with a percentage of 71.42%. Based on these data, it can be concluded that the use of the Project Based Learning model can improve the ability to compose biographical texts for class X students at State High School 1 Majene, Regency.